Formal policy and informal process in the implementation of juvenile justice reform - Bazemore, Gordon (Criminal justice review, 1993)
The study of policy and program implementation has advanced significantly in the past two decades, but relatively little attention has been paid to the complex issues involved in expanding promising local models for reforming justice agencies to other jurisdictions. This paper examines statewide implementation of a legislatively mandated reform intended to restrict and rationalize the use of juvenile detention based on a successful local model. Though statewide aggregate data indicate initial success in the use of formal intake criteria to reduce secure detention populations, early revisions of a risk assessment instrument used to objectively determine restrictiveness levels signify concern on the part of some decision makers to restore discretion over the use of secure detention. Detention intake data from one county facility are used to illustrate the potential impact of these changes on detention populations and to explore the role of informal processes, as well as that of formal criteria, as a key factor in expanding the implementation of local reforms